2016
DOI: 10.1021/jacs.5b11688
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic Ordering-Induced Multiferroic Behavior in [CH3NH3][Co(HCOO)3] Metal–Organic Framework

Abstract: We present the first example of magnetic ordering-induced multiferroic behavior in a metal-organic framework magnet. This compound is [CH3NH3][Co(HCOO)3] with a perovskite-like structure. The A-site [CH3NH3](+) cation strongly distorts the framework, allowing anisotropic magnetic and electric behavior and coupling between them to occur. This material is a spin canted antiferromagnet below 15.9 K with a weak ferromagnetic component attributable to Dzyaloshinskii-Moriya (DM) interactions and experiences a discon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

8
157
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 177 publications
(166 citation statements)
references
References 39 publications
8
157
1
Order By: Relevance
“…The IR reflection spectra of the 13 EtACd crystal have been fitted using the four-parameter model. Information about LO and TO wavenumbers can be received from fitting the IR reflection spectra by using a fourparameter model [40].…”
Section: Figurementioning
confidence: 99%
See 1 more Smart Citation
“…The IR reflection spectra of the 13 EtACd crystal have been fitted using the four-parameter model. Information about LO and TO wavenumbers can be received from fitting the IR reflection spectra by using a fourparameter model [40].…”
Section: Figurementioning
confidence: 99%
“…The best known examples are compounds of general formula [cat][M(HCOO)3], where M = Mn, Ni, 3 Co, Fe, and cat denotes ammonium, methylammonium, dimethylammonium (DMA), guanidinium (Gua), formamidinium (FMD) or azetidinium cation [3][4][5][6][7][8][9][10][11][12][13][14][15][16][17]. Many of [cat][M(HCOO)3] compounds undergo structural phase transitions, which are often associated with the appearance of electric order and pronounced dielectric anomalies [8][9][10][11][12][13][14][15][16][17]. It is worth to mention that up to now the highest phase transition temperature (435 K) in the family of dense MOFs has been found for imidazolium analogue, [C3N2H5][Mn(HCOO)3] [14].…”
Section: Introductionmentioning
confidence: 99%
“…Remarkable examples are, for instance, (CH 3 NH 3 )PbI 3 and related compounds2526, which exhibit exceptional optoelectronic properties for photovoltaic applications. And also the [AmineH][M(X) 3 ] perovskite families (AmineH=midsized protonated amines, M=divalent transition metal cations, X=bidentate-bridge ligands HCOO − , N 3 − , CN − , and so on) which display outstanding functionalities such as cooperative magnetic, electric and/or elastic order, and magnetically induced multiferroicity; moreover, they can also act as precursors for different nanostructured functional materials272829303132333435363738.…”
mentioning
confidence: 99%
“…7,8 In perovskite MOFs compounds, the electronic and magnetic properties associated with order/disorder transitions of the [AmineH] + cations and the framework [M(HCOO) 3 ] -, respectively. [9][10][11] So the perovskite MOFs materials can be suitable candidates, as single-phase multiferroic materials with excellent electronic and magnetic properties. [12][13][14][15][16] It has been reported that the MOFs materials with different A (different size, type) exhibit different physical properties.…”
Section: Introductionmentioning
confidence: 99%
“…[21][22][23] The property of ferroelectricity induced by magnetic order was also found in the metal-organic framework magnet [CH 3 NH 3 ][Co(HCOO) 3 ]. 9,24 Recently, Ren-Gen Xiong and his team reported that the para-toferroelectricity occurred in range of 3 ] series, which the disorder-order transition of (CH 3 ) 2 NH 2 + template could be the origin of electric ordering. 25,26 On the other hand, the magnetoelectric effect could exist in the materials with the A of C(NH 2 ) 3 However, the disorder-order transition usually appears at very low temperature among these MOFs materials.…”
Section: Introductionmentioning
confidence: 99%